The Saharan Air Layer as an Early Rainfall Season Suppressant in the Eastern Caribbean: The 2015 Puerto Rico Drought. Issue 20 (30th October 2017) - Mote, Thomas L.; Ramseyer, Craig A.; Miller, Paul W.
Abstract: Eastern Puerto Rico and the surrounding Caribbean experienced a severe drought in 2015 that resulted in record‐low reservoir and river levels. Rainfall deficits in April and May, which represent the period when the drought began, were more severe in 2015 than recent droughts of record. While El Niño has been associated with drought in the Caribbean, onset of the 2015 drought was strongly associated with lower‐than‐average values of a recently developed tool used by weather forecasters in San Juan, the Gálvez‐Davison Index (GDI), which is used to measure the potential for thunderstorm development and rainfall. Persistently low GDI values indicate strong and frequent intrusions of hot, dry air in the low to middle troposphere, suppressing convection, both locally and in development regions for tropical waves that impact Puerto Rico. The Saharan Air Layer (SAL) is largely responsible for this anomalously hot, dry air, which produced thermodynamically stable conditions and limited thunderstorms and rainfall. Moreover, higher‐than‐normal aerosol concentrations, typically associated with SAL intrusion over the Caribbean, were recorded in April and May 2015. A comparison to advanced very high resolution radiometer aerosol optical thickness demonstrates that higher Caribbean aerosols in the early rainfall season, particularly June, are associated with decreased rainfall in eastern Puerto Rico. Results here demonstrate a direct link between the early and more pronounced SAL intrusions into the Caribbean and the suppression of the early rainfall season. More broadly, a reduction in the GDI and increase in the trade wind inversion was associated with reduced early season rainfall in the eastern Caribbean. Key Points: Results demonstrate a link between the early and more pronounced 2015 Saharan Air Layer intrusions into the Caribbean and the suppression of the early rainfall season in Puerto Rico The Saharan Air Layer is identified by an anomalously low Gálvez‐Davison Index, stronger trade wind inversion, and increased aerosol loadings and is associated with reduced early season rainfall in the eastern Caribbean Plain Language Summary: The eastern Caribbean, and specifically eastern Puerto Rico, suffered a severe drought in 2015. While discussion in the media and among professionals indicated the drought was associated with El Nino, the role of Saharan dust received relatively little attention. This research demonstrates that Saharan dust arrived early in the Caribbean in 2015 and resulted in conditions that were unfavorable for rainfall. Further analysis demonstrates that the early rainfall season (April‐July) in eastern Puerto Rico is strongly related to conditions associated with Saharan dust intrusions, which were identified using a tool commonly used by operational weather forecasters in Puerto Rico.